MARKET STRUCTURE, CONDUCT AND PERFORMANCE: EVIDENCE FROM INDONESIA BANKING INDUSTRY - Rizky Yudaruddin (EKUITAS (Jurnal Ekonomi dan Keuangan), 2015)
Indonesian Banking Architecture Policies (API) since 2004 has resulted in the rising of banks concentration. This increase of banks concentration raises two opposing hypotheses,structure-conduct- performance (SCP) and efficient-performance hypothesis. SCP approach is a structural approach. This approach considers that the level of profits which the bank acquired is affected by the market structure and the degree of competition.The decreasing level of competition and the increasing in concentration in an industry will lead to increased profits for these industries.This study aims to prove, whether banks in Indonesia in 2009-2013 supportstructure-conduct-performanceor efficient-performance hypotheses. The sampling method used was purposive sampling. Using banks’ financial statement data sourced fromBank Indonesia, which then analyzed with panel data regression in e-views 8 program. It’s found that banks in Indonesia support the efficient hypothesis. However, the banks efficiency has yet encourage low interest practice and thus reducing the competitiveness of the Indonesian economy in the face ofASEAN Community 2015.